Amotivation in physical activity of the population over 15 years of Monterrey (Mexico) - Jeanette Magnolia López Walle; Marco Antonio Garrido Salazar; Jorge Isabel Zamarripa Rivera; Francisco Ruiz Juan (FEADEF, 2011)
The aim of this paper is to describe the reasons that have given origin to the amotivation of Monterrey adult citizens that have not done any physical activity according to gender, age and the level of studies. The sample was estimated in 1,118 subjects to obtain result validity with an error range of ±3% and a reliability level of 95.5%. The sample procedure used has been multistage with a proportional affixation, resorting to two types of stratificated random sampling by conglomerates. Results reveal that the values beliefs were the ones generating the amotivation to never have practiced any physical activity on leisure time of the subjects from 30 to 44 years old with high school finished